Pengaruh Sistem Informasi Akuntansi, E-Commerce, Insentif Pajak, dan Bantuan Stimulus Pemerintah pada Kinerja UMKM - Sri Ayem; Putri Shalsya Bilah Nasir (Journal on Education, 2024)
This research aims to determine the influence of accounting information systems, e-commerce, tax incentives and government stimulus assistance on the performance of MSMEs. The research method uses primary data and the data collection method uses questionnaire techniques. The population in this research is all Micro, Small and Medium Enterprises (MSMEs) in the City of Yogyakarta. The sampling technique used probability sampling which was obtained through distributing questionnaires so that 100 respondents were obtained. The results show that the accounting information system and government stimulus assistance have a positive effect on the performance of MSMEs; while e-commerce and tax incentives have a negative effect on MSME performance. This research can be reference for MSME players to improve MSME performance by paying attention to use of accounting information systems, e-commerce, tax incentives and government stimulus assistance used in operations as well as paying attention to the quality of human resources in their management.